Optimal combinable and dedicated energy crop scenarios for marginal land - Glithero, N.J.; Wilson, Paul; Ramsden, Stephen J. (Elsevier, 2015)
Modern biomass energy sources account for less than 2% of primary world energy supplies while major economies have enabled legislation that aims to increase bioenergy production. In response to controversies over first generation biofuel, it has been argued that ‘marginal land’ should be used to produce dedicated energy crops (DECs). However, defining marginality of agricultural land is complex, and moreover, DECs would have to out-compete current agricultural production in these areas. Utilising a bio-economic farm-level modelling approach we investigate the impact that crop yield penalties resulting from production in marginal land contexts have on financially optimal farm-level crop plans. Where farm businesses choose to de-invest in own farm machinery, yield reductions of less than 10% for winter wheat result in a financially optimal switch to 100% miscanthus production. By contrast, in the presence of own farm machinery, winter wheat yield penalties of 30% are required before 100% miscanthus production is financially optimal. However, under circumstances where DECs also suffer yield penalties on marginal land, the financially optimal crop mix includes combinable crops. The results demonstrate that the optimal crop mix is dependent upon the relative combinable and DEC yields, together with farm-level decisions towards machinery ownership. The focus of much policy attention relating to production of DECs on ‘marginal land’ is therefore argued to be incomplete. Policies which encourage farmers to de-invest in own farm machinery, or incentivise the purchase of specific DEC machinery, may play an important role in assisting the development of DEC production.